Integrated Model of the Higher Education Financing Under the Quadruple Helix Concept - Kholiavko, N; Zhavoronok, A; Shaposhnykov, K; Krylov, D; Morozova, L; Babiak, N (International Journal of Computer Science and Network Security, 2021)
Rapid growth of the higher education role in ensuring the socioeconomic and innovative development of the national economy in the context of the development of the information society and the knowledge economy is observed. Achieving positive synergistic effects of the higher education development requires proper funding for university education and research. The existing funding models for national higher education systems in a number of developing countries need modernization in accordance with the modern challenges of economic and innovative development. The purpose of the article is to formulate theoretical – methodological and applied foundations for the development and implementation of the integrated model of the higher education financing under the Quadruple Helix concept. At the center of the developed model are the areas of interaction identified by the authors, namely: Personnel, Science, Management, Innovation, Social area. This made it possible to specify the interests of all stakeholders and orient the activities of higher education institutions to the satisfaction of these interests. Effective implementation of the integrated Model of the higher education financing requires increasing the level of investment attractiveness and practical value of university research; activation of innovative development of enterprises; state stimulation of business participation in university research and education; harmonization of current legislation with EU standards. Implementation of the Model will diversify sources of funding for universities, increase their level of economic security and achieve integrated synergies from the interaction of universities, business, government and the public (as the main stakeholders within the Quadruple Helix concept).
Keywords: higher education; Quadruple Helix concept; integrated model of financing; diversification of funding sources; R&D commercialization.